Impact of tranexamic acid on the efficacy of vancomycin and meropenem against periprosthetic joint infections: an in vitro analysis - Liqin Yao; Youcai Ma; Qiangde Hu; Rui Liu; Boyong Xu; Xuebin Sun; Li Cao; Wenbo Mu (Bone & Joint Research)
Aims: This study investigated the effects of tranexamic acid (TXA) on the efficacy of vancomycin and meropenem against common periprosthetic joint infection (PJI)-associated pathogens in vitro. The aim was to uncover valuable insights that can be used for clinical decision-making and enhanced management of PJI in orthopaedic surgery. Methods: We evaluated the minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), minimum biofilm inhibitory concentration (MBIC), and minimum biofilm eradication concentration (MBEC) for vancomycin and meropenem, both with and without TXA, against various bacterial strains. Results: In the planktonic bacterial phase, TXA increased the MIC and MBC of vancomycin for Staphylococcus aureus and Staphylococcus epidermidis, decreased the MIC and MBC of meropenem for S. aureus, and increased the MIC and MBC of vancomycin combined with meropenem for S. aureus. In biofilms, TXA in combination with vancomycin synergistically decreased the MBIC and MBEC values of methicillin-resistant S. aureus (MRSA) and S. aureus. Conclusion: TXA influences antibiotic efficacy against both planktonic bacteria and biofilms, with effects varying by antibiotic and bacterial strain. These findings underscore the complexity of drug interactions in PJI treatment, highlighting the need for tailored therapeutic strategies based on strain-specific responses. Cite this article: Bone Joint Res 2025;14(7):601–608.